Genome sequencing with comprehensive variant calling identifies structural variants and repeat expansions in a large fraction of individuals with ataxia and/or neuromuscular disorders - Ek, Marlene; Nilsson, Daniel; Engvall, Martin; Malmgren, Helena; Thonberg, Håkan; Pettersson, Maria; Anderlid, Britt-Marie; Hammarsjö, Anna; Helgadottir, Hafdis T.; Arnardottir, Snjolaug; Naess, Karin; Nennesmo, Inger; et al. (Frontiers in Neurology, 2023)
Introduction Neuromuscular disorders (NMDs) have a heterogeneous etiology. A genetic diagnosis is key to personalized healthcare and access to targeted treatment for the affected individuals. Methods In this study, 861 patients with NMDs were analyzed with genome sequencing and comprehensive variant calling including single nucleotide variants, small insertions/deletions (SNVs/INDELs), and structural variants (SVs) in a panel of 895 NMD genes, as well as short tandem repeat expansions (STRs) at 28 loci. In addition, for unsolved cases with an unspecific clinical presentation, the analysis of a panel with OMIM disease genes was added. Results In the cohort, 27% (232/861) of the patients harbored pathogenic variants, of which STRs and SVs accounted for one-third of the patients (71/232). The variants were found in 107 different NMD genes. Furthermore, 18 pediatric patients harbored pathogenic variants in non-NMD genes. Discussion Our results highlight that for children with unspecific hypotonia, a genome-wide analysis rather than a disease-based gene panel should be considered as a diagnostic approach. More importantly, our results clearly show that it is crucial to include STR- and SV-analyses in the diagnostics of patients with neuromuscular disorders.